The Relative Importance of Labour Market Reforms to Economic Growth - Karl Aiginger (Austrian Institute of Economic Research (WIFO), 2003)
Insufficiently flexible labour markets combined with high welfare costs are often thought to be the main cause of unsatisfactory growth in Europe. This paper uses the OECD data on regulation of the product and labour market to confirm the difference in the extent of regulation between US and Europe in labour and product market regulation. However, there are at least two other explanations for European underperformance during the nineties: insufficient investment in long run determinants of growth and macroeconomic policy. We first show that European policy differed from that of the US in all three areas. The extent of the differences is decreasing for labour market regulation, but increasing for macroeconomic policy and for investment into future growth. Then we exploit performance differences between European countries to assess the relative importance of labour market reforms versus investment into long-run growth. The best performing European countries did fine tune incentives in labour and product markets, without dismantling the welfare regime and with little deregulation for regular labour contracts. The largest continental economies - Germany, France and Italy - did not reform their institutions to the same extent. However the main difference between the top 3 and the big 3 countries is the increasing investment of the successful countries into the determinants of long run growth. This indicates that labour market regulation may be an important condition for growth, while investment into research, innovation and new technologies is the sufficient condition.
Keywords: E60; O11; O40; 330; Labour market reforms; market regulation; economic growth; transatlantic differences; Arbeitsmarktpolitik; Arbeitsmarkt; Wirtschaftswachstum; Länderbericht; EU-Staaten; USA